RESEARCH ON CLINICAL AND PARACLINICAL CHARACTERISTICS OF CANDIDEMIA AT VIET TIEP FRIENDSHIP HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Background: Candidemia is a leading cause of invasive fungal infections in hospitals, particularly among critically ill patients, the elderly, and those with multiple comorbidities or immunosuppression. Objectives: This study aimed to describe the epidemiological, clinical, and laboratory characteristics of candidemia and analyze factors associated with treatment outcomes at Viet Tiep Friendship Hospital.Methods: A retrospective cross‑sectional study was conducted on 34 patients with positive blood cultures for Candida spp between October 2024 and September 2025. Clinical data, laboratory findings, and microbiological results were extracted from medical records.Results: The mean age was 65.3 ± 16.7 years; 73.5% were male. The most common comorbidities were: cardiovascular disease (52.9%), diabetes mellitus (50%), cerebrovascular disease (26.5%), chronic kidney disease (20.6%). The most clinical features: fever (85.3%), pneumonia (79.4%), septic shock (47.1%), respiratory failure (38.2%). Microbiology: Non‑albicans Candida predominated (70.6%), with C. tropicalis (26.5%) and C. parapsilosis (23.5%) most frequent. Clinical outcomes includes: recovery in 29.4%, deterioration in 23.5%, and mortality in 14.7%.Conclusion: Candidemia at Viet Tiep Hospital is characterized by high morbidity in elderly ICU patients with significant comorbidities. Candidemia present with severe clinical manifestations, with mortality and deterioration rates exceeding one-third of patients (38.2%). And non – albicans Candida predominated (70.6%). Early recognition of risk factors, timely diagnosis, appropriate antifungal therapy, and strict infection control measures are essential to reduce complications and mortality.
Keywords: candidemia, invasive candida infection, antifungal